Pathogenicity of novel variant infectious bursal disease virus in commercial broiler chickens - Chong, Hao Han
Infectious bursal disease (IBD) has presented significant challenges to the poultry industry, resulting in substantial economic losses due to high mortality and its immunosuppressive effects. The emergence of a new variant, novel variant infectious bursal disease virus (nVarIBDV), has exacerbated the situation, especially since existing IBD vaccines fail to provide adequate immunity against this strain. This study aimed to explore the pathogenicity of nVarIBDV in commercial broiler chickens. Sixty, three-week-old commercial broiler chicks were divided into two groups: the nVarIBDV group (28/60) and the control group (32/60). On 0 days post-inoculation (dpi), the nVarIBDV group received a 1.0 mL inoculation containing 106.75 EID50 of nVarIBDV, administered via eye drops (0.1 mL) and orally (0.9 mL), while the control group remained uninoculated. Samples were taken from both groups at 0, 1, 3, 5, 7, 10, 14, and 21 dpi, with only the control group sampled on 0 dpi. Throughout the study, clinical signs, body weight, bursa, and spleen weights were measured. IBD antibody titer was analysed through ELISA, and RT-qPCR analyses were conducted on samples from the bursa, spleen, caecal tonsil, thymus, and bone marrow. Neither group displayed clinical symptoms, but there was negative impact on body weight of chicken inoculated with nVarIBDV. Upon necropsy, the nVarIBDV group exhibited bursal atrophy and decreased bursal weight, supported by BBIX values below 0.7 from 3 to 21 dpi. The bursa of Fabricius (BF) in the control group appeared normal, while the nVarIBDV group displayed moderate to severe bursal lesions, with scores significantly (p<0.05) higher than the control group. The bursa histopathological analysis in nVarIBDV group revealed degeneration of lymphoid follicle, infiltration of inflammatory cells into interstitial space, thickened and vacuolated epithelium, and follicular cyst formation. Additionally, splenomegaly was observed from 3 to 5 dpi in response to nVarIBDV infection. The IBD antibody titer in nVarIBDV group increased starting from 5 dpi, reaching very high peak on 10 dpi and remained high until 21 dpi, in contrast to the consistently very low titer in the control group. In RT-qPCR analysis, the bursa of nVarIBDV-inoculated chickens exhibited the highest viral loads among the studied organs, highlighting the bursa as the primary target organ for nVarIBDV. In conclusion, the nVarIBDV is pathogenic and cause subclinical disease without mortality in commercial broiler chickens, body weight dropping, severe bursal atrophy, splenomegaly, high antibody response and increased viral loads in the organs.